Large-area 11.75% efficient vertical graphene nanowalls/textured silicon Schottky junction solar cell based on PEDOT:Nafion doping scheme. (1st March 2023) - Cui, Yiqian; Zhang, Lukai; Liu, Linqing; Jia, Lizhe; Zhang, Yu; Yu, Wei
Abstract: Preparing large areas of graphene on textured silicon is necessary for the industrialization of graphene/silicon solar cells. However, many passivation films with insulating properties prepared by the solution method are not applicable for the textured structures as the insulation areas are easily formed at the bottom of the pyramid. In this paper, we prepare large-area vertical graphene nanowalls (VGNWs) on textured c-Si by plasma-enhanced chemical vapor deposition (PECVD) and introduce conductive-passivating poly(3, 4-ethylenedioxythiophene) (PEDOT):Nafion composite thin films to modify the textured VGNWs/Si Schottky junction. The formation of insulation areas was avoided. Moreover, the reflectivity was reduced to less than 7% as the superposition of textured structures and PEDOT:Nafion film. After applying an interfacial layer of Al2 O3, the cell efficiency was increased to 11.75%, with a large active area of 0.64 cm 2 . This work will promote the industrialization of VGNWs/Si solar cells.